2011
DOI: 10.2134/jeq2010.0317
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Soil Texture and Placement of Dairy Slurry Application: I. Flow Characteristics and Leaching of Nonreactive Components

Abstract: Land application of manure can exacerbate nutrient and contaminant transfers to the aquatic environment. This study examined the effect of injecting a dairy cattle (Bostaurus L.) manure slurry on mobilization and leaching of dissolved, nonreactive slurry components across a range of agricultural soils. We compared leaching of slurry-applied bromide through intact soil columns (20 cm diam., 20 cm high) of differing textures following surface application or injection of slurry. The volumetric fraction of soil po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 25 publications
6
56
1
Order By: Relevance
“…Indeed, our results showed deep infiltration into clay soils through preferential flow with very low interaction. This is consistent with other literature that has shown preferential flow to increase in occurrence in soils with increasing clay content (Djodjic et al, ; Glaesner et al, ). Grant et al () also found preferential flow to occur through clay soil, under both frozen and thawed conditions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, our results showed deep infiltration into clay soils through preferential flow with very low interaction. This is consistent with other literature that has shown preferential flow to increase in occurrence in soils with increasing clay content (Djodjic et al, ; Glaesner et al, ). Grant et al () also found preferential flow to occur through clay soil, under both frozen and thawed conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Additional work has shown that the subsurface placement of nutrients can reduce P loss in surface run‐off (Smith et al, ) and subsurface drainage (Grant, Macrae, Rezanezhad, & Lam, ; Williams, King, Duncan, Pease, & Penn, ). The placement of nutrients in the subsurface may increase the interaction between applied nutrients and the soil, thereby increasing chemical retention of nutrients in the soil (Glaesner, Kjaergaard, Rubaek, & Magid, ; Williams et al, ), whereas nutrients broadcast over no‐till soils have little contact with the soil and can easily be lost (Feyereisen et al, ; Kleinman et al, ). Further, it has been suggested that placement of nutrients in the subsurface reduces the risk of contact of applied nutrients with preferential flowpaths, therefore limiting nutrient leaching (Glaesner, Kjaergaard, Rubaek, & Magid, ).…”
Section: Introductionmentioning
confidence: 99%
“…The plot had not received any animal manure in the previous 2 years. Sampling was done using stainless steel cylinders (length, 20 cm; diameter, 20 cm) as described previously (33). The soil columns were slowly saturated and then drained to a soil water potential of Ϫ100 hPa, i.e., close to field capacity for this soil.…”
Section: Soilsmentioning
confidence: 99%
“…The initial 1-week delay between slurry application and IE1 was chosen to simulate conditions in the field where slurry is typically applied during a dry spell in spring. Artificial rainwater (0.1 mM NaCl, 0.01 mM CaCl 2 Ϫ1 was applied using a rain simulator (33,36). During these events the soil columns with or without slurry rested on a glass filter disc of 60-to 100-m pore size and 1.6-cm thickness (ROBU; Glasfilter Geräte GMBH, Germany).…”
Section: Soilsmentioning
confidence: 99%
“…). Like on the middle slope, the silty substrata can hold high amounts of immobile water ( Blume et al, ; Glaesner et al, ). This favors intensive P mobilization and, after drying, the formation of P dHCl .…”
Section: Discussionmentioning
confidence: 99%